Menumbuhkan Kemandirian Ekonomi Perempuan Jama’ah Masjid: Optimalisasi Wakaf Produktif dan Literasi Pemasaran Digital - Sari Purwaning Rum; Fitroh Adhilla; Salamatun Asakdiyah; Ema Nurmaya (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
This community service program aims to foster the economic independence of female congregants at Al-Hidayah Mosque, Gunungkidul Regency, through the integration of productive waqf management and digital marketing literacy. The program targets 38 female congregants in Gupakan Hamlet, utilizing a total sampling method identified via SWOT analysis to address limited digital literacy and the risks of karst land degradation. The implementation follows an integrated socialization approach based on the POAC framework (Planning, Organizing, Actuating, and Controlling). Program effectiveness was evaluated using a One-Group Pretest-Posttest design with a single-questionnaire instrument, which directly integrates both integrated farming and digital marketing modules, to mitigate respondent fatigue without compromising data accuracy. The instrument demonstrated high reliability with a Cronbach’s Alpha of 0.724. Results from the Normalized Gain (N-Gain) analysis indicate a significant increase in knowledge with a score of 0.7648 (high category), comprising improved understanding of integrated farming (82%) and digital marketing (84%). The empirical impact is further evidenced by the formulation of land management plans and a 100% written commitment from participants to implement environmental conservation practices. This program successfully reduced social resistance through total congregational acceptance (100%) of transparent business waqf governance, while simultaneously narrowing the gender gap by actively involving women as mosque administrators who are independent and competitive in the digital era.